Integrating Radiologic and Clinical Features to Predict VSX1 Expression in Clear Cell Renal Cell Carcinoma. - Greco, Federico; Panunzio, Andrea; Sergi, Daniele; Cataldo, Marco; Bernetti, Caterina; Tafuri, Alessandro; Beomonte Zobel, Bruno; Mallio, Carlo Augusto (Current Oncology, 2025)
Simple Summary: Clear cell renal cell carcinoma is the most common type of kidney cancer and can show aggressive behavior. Recent research suggests that the gene VSX1 is associated with worse outcomes in these tumors. In this study, we analyzed CT scans and clinical data from 194 patients to investigate whether specific imaging features are linked to VSX1 expression. We found that VSX1-positive tumors were more common in male patients and were associated with tumor necrosis greater than 66%, collecting system invasion, and perinephric adipose tissue stranding. Based on these features, we created a predictive score to estimate the likelihood of VSX1 expression. This non-invasive method may help clinicians identify patients with a more aggressive tumor profile and guide personalized treatment strategies. Background: Visual system homeobox 1 (VSX1) is a transcription factor recently implicated in promoting tumor aggressiveness in clear cell renal cell carcinoma (ccRCC). While its molecular role is emerging, the radiogenomic characteristics associated with VSX1 expression remain unexplored. This study aims to investigate the computed tomography (CT) imaging features linked to VSX1 expression, hypothesizing a correlation with radiologic markers of aggressive tumor behavior. Methods: A retrospective analysis was conducted using imaging and clinical data from 194 ccRCC patients obtained from The Cancer Genome Atlas and The Cancer Imaging Archive. CT scans were evaluated for multiple tumor characteristics, including necrosis, collecting system invasion, and perinephric fat stranding. Patients were stratified into VSX1-positive and -negative groups. A Lasso logistic regression model was applied to identify the most predictive imaging and clinical variables associated with VSX1 expression. A predictive score and probability nomogram were developed and evaluated. Results: VSX1 expression was positive in 19.1% of patients. Key features significantly associated with VSX1 positivity included male sex, tumor necrosis > 66%, collecting system invasion, and perinephric fat stranding. The Lasso model demonstrated good discriminatory power (area under the curve 0.75), and the predictive score effectively stratified patients based on estimated expression risk. Conclusions: VSX1-positive ccRCC presents with a distinct radiogenomic phenotype marked by imaging features of known aggressiveness. The integration of radiologic and genomic data allows for non-invasive risk stratification and may inform future personalized therapeutic strategies. External validation is needed to confirm clinical applicability.